Monetary Policy and Herding Behavior: Empirical Evidence From Indonesia Stock Market - Wicaksono, Retno Puspita K.; Falianty, Telisa Aulia (UI Scholars Hub, 2022)
This study aims to analyze the role of monetary policy, including the spillover of the US Federal Reserve (Fed) monetary policy, in the existence of herding behavior in the Indonesian stock market. We used beta herding to measure the level of herding behavior and analyze the relationship between monetary policy and beta herding using the VECM model, as well as IRF and FEVD. This study shows that monetary policy plays a role in the existence of herding behavior in the Indonesian stock market. Although the effect of monetary policy on herding behavior is relatively small, Fed monetary policy shocks have a greater effect on the existence of herding behavior in the Indonesian stock market. The credibility of Bank Indonesia (BI) and the Fed may play a role in shaping investors’ expectations. Therefore, policymakers have to take into account the volatility of asset prices in formulating monetary policy